Studying the Aspects of Knowledge Creation in the LAB Studio Model - Kari-Pekka Heikkinen; Teppo Räisänen (International School for Social and Business Studies, 2016)
The organisations of higher education are constantly changing. Universities, colleges, private schools and online universities refine their pedagogical methods and learning models in a competitive market. This article is a study on whether one such model helps students to gain new knowledge. A study of the LAB studio model (LSM), which is a pedagogical model developing connections between working-life based problems and the recognition and development of business-related prototypes and start-up companies, is presented. The LSM, theoretically grounded in a constructivist view of learning with a project-based education at its core, has the key goal of educating entrepreneurial competences in higher education. Based on the case study, comprisinga literature review of knowledge creation and a survey, the qualitative results analysis suggests that LSM offers a promising support for knowledge creation. The results lead to the conclusion that LSM provides support especially for the various modes of the SECI model, such as socialisation and internalisation, and seems to support organisational knowledge creation aspects as well.